Direct evaluation of boson dynamics via finite-temperature time-dependent variation with multiple Davydov states - Fujihashi, Yuta (2019)
Recent advances in quantum optics allow for exploration of boson dynamics in dissipative many-body systems. However, the traditional descriptions of quantum dissipation using reduced density matrices are unable to capture explicit information of bath dynamics. In this work, efficient evaluation of boson dynamics is demonstrated by combining the multiple Davydov Ansatz with finite-temperature time-dependent variation, going beyond what state-of-the-art density matrix approaches are capable to offer for coupled electron-boson systems. To this end, applications are made to excitation energy transfer in photosynthetic systems, singlet fission in organic thin films, and circuit quantum electrodynamics in superconducting devices. Thanks to the multiple Davydov Ansatz, our analysis of boson dynamics leads to clear revelation of boson modes strongly coupled to electronic states, as well as in-depth description of polaron creation and destruction in the presence of thermal fluctuations.